Investigation of Liquid Water Distribution under Temperature Gradient in PEFC Using in-situ X-ray Visualization. (8th September 2020) - Komiyama, Takahiro; Sasabe, Takashi; Naito, Hiroshi; Kawamura, Katsuyuki; Suzuki, Toshiyuki; Hirai, Shuichiro
Abstract : Polymer electrolyte fuel cells (PEFCs) are one of promising electric generating devices. It is necessary to understand the relationships between the water distribution and the temperature distribution in gas diffusion layers (GDLs) to improve the performance at high current density. To reveal the effects of cell temperature on liquid water accumulation inside PEFCs, in-situ X-ray measurement and numerical simulation were performed at 40, 60, 70, and 80°C. The measurement was carried out using a fuel cell having a serpentine-type flow field, ribs and flow channels of 300 μm width, and 1.5×3.0mm 2 active area. Current density was kept 1.5 A/cm 2 for 300 secs in all cases. Both the experimental results and the numerical results showed that the liquid water distribution in GDLs strongly depends on cell temperature. In the case of lower temperature, liquid water accumulated in a region near CL and MPL. While in the case of higher temperature, liquid water accumulated in a region near rib. In addition, the experimental results indicated that the vapor crossover depended on existence of liquid water in MPL, and it was shown that the amount of vapor crossover increased at lower temperature condition.